2022
DOI: 10.3389/esss.2022.10054
|View full text |Cite
|
Sign up to set email alerts
|

Time Zero for Net Zero: A Coal Mine Baseline for Decarbonising Heat

Abstract: Mine water geothermal energy could provide sustainable heating, cooling and storage to assist in the decarbonisation of heat and achieving Net Zero carbon emissions. However, mined environments are highly complex and we currently lack the understanding to confidently enable a widespread, cost-effective deployment of the technology. Extensive and repeated use of the mined subsurface as a thermal source/store and the optimisation of operational infrastructure encompasses a range of scientific and technical chall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Many of the towns and cities in the UK and across Europe are areas of former coal mining activity and the shallow flooded mine workings are prospective to heat local homes and businesses (Walls et al, 2021). Projects worldwide have demonstrated mine water heating, cooling and inter-seasonal storage (Walls et al, 2021) and widespread scale up is anticipated (Watson et al, 2019;Monaghan et al, 2022).…”
Section: Minewater Geothermal Energy (Mwge) and Its Potential To Deca...mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the towns and cities in the UK and across Europe are areas of former coal mining activity and the shallow flooded mine workings are prospective to heat local homes and businesses (Walls et al, 2021). Projects worldwide have demonstrated mine water heating, cooling and inter-seasonal storage (Walls et al, 2021) and widespread scale up is anticipated (Watson et al, 2019;Monaghan et al, 2022).…”
Section: Minewater Geothermal Energy (Mwge) and Its Potential To Deca...mentioning
confidence: 99%
“…• While MWGE is an emerging technology, global resource estimates are large (Monaghan et al, 2022). There is particular interest in minewater geothermal in the UK and Europe as a pathway to accelerate heat decarbonisation: there is significant potential for MWGE projects to provide low carbon heat to homes and businesses local to the resource (Watson et al, 2019;Abesser and Walker, 2022).…”
Section: Minewater Geothermal Energy (Mwge) and Its Potential To Deca...mentioning
confidence: 99%
“…The use of thermal energy contained within groundwater in abandoned, flooded, coal mines has considerable potential to contribute to the provision of low carbon heating or cooling to assist in meeting global net-zero carbon emission targets (Adams et al, 2019;Stephenson et al, 2019;Monaghan et al, 2022a). A quarter of UK homes and businesses lie above former coalfields, providing a highly permeable network of buried mine workings flooded with water at above-ambient temperatures (Adams et al, 2019;Monaghan et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…The use of open loop abstraction-reinjection (well doublet) heat exchange systems based on shallow groundwater is globally widespread (Jessop et al, 1995;Verhoeven et al, 2014;Ramos et al, 2015;Walls et al, 2021;Monaghan et al, 2022a;Banks et al, 2022), and is similar to configurations found in other geothermal reservoir types such as hot dry rock and hot sedimentary aquifers (Limberger et al, 2018;Reinecker et al, 2021). However, there are alternative configurations by which mine water's thermal energy can be harnessed (Banks et al, 2019;Walls et al, 2021), each accompanied by varying drilling costs and project risks (Monaghan et al, 2022b).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are alternative configurations by which mine water's thermal energy can be harnessed (Banks et al, 2019;Walls et al, 2021), each accompanied by varying drilling costs and project risks (Monaghan et al, 2022b). Detailed understanding of mine water geothermal energy resource size and sustainability remains largely in its research phase, with increasing numbers of projects being started (Walls et al, 2021;Monaghan et al, 2022a;Banks et al, 2022). Owing to the heterogeneous nature of mine workings, each project has unique hydrogeological properties, thus uncertainty around the speed and extent of heat migration within mines and initial resource scale and availability are regarded as significant project risks during the planning stage (Walls et al, 2021).…”
Section: Introductionmentioning
confidence: 99%